Final Results of an EORTC-GU Cancers Group Randomized Study of Maintenance Bacillus Calmette-Guerin in Intermediate- and High-risk Ta, T1 Papillary Carcinoma of the Urinary Bladder: One-third Dose Versus Full Dose and 1 Year Versus 3 Years of Maintenance - (:unkn) unknown (ELSEVIER SCIENCE BV, 2013)
Background: The optimal dose and duration of intravesical bacillus Calmette-Guerin (BCG) in the treatment of non-muscle-invasive bladder cancer (NMIBC) are controversial. Objective: To determine if a one-third dose (1/3D) is not inferior to the full dose (FD), if 1 yr of maintenance is not inferior to 3 yr of maintenance, and if 1/3D and 1 yr of maintenance are associated with less toxicity. Design, setting, and participants: After transurethral resection, intermediate-and high-risk NMIBC patients were randomized to one of four BCG groups: 1/3D-1 yr, 1/3D-3 yr, FD-1 yr, and FD-3 yr. Outcome measurements and statistical analysis: The trial was designed as a noninferiority study with the null hypothesis of a 10% decrease in the disease-free rate at 5 yr. Times to events were estimated using cumulative incidence functions and compared using the Cox proportional hazards regression model. Results and limitations: In an intention-to-treat analysis of 1355 patients with a median follow-up of 7.1 yr, there were no significant differences in toxicity between 1/3D and FD. The null hypotheses of inferiority of the disease-free interval for both 1/3D and 1 yr could not be rejected. We found that 1/3D-1 yr is suboptimal compared with FD-3 yr (hazard ratio [HR]: 0.75; 95% confidence interval [CI], 0.59-0.94; p = 0.01). Intermediate-risk patients treated with FD do not benefit from an additional 2 yr of BCG. In high-risk patients, 3 yr is associated with a reduction in recurrence (HR: 1.61; 95% CI, 1.13-2.30; p = 0.009) but only when given at FD. There were no differences in progression or survival. Conclusions: There were no differences in toxicity between 1/3D and FD. Intermediate-risk patients should be treated with FD-1 yr. In high-risk patients, FD-3 yr reduces recurrences as compared with FD-1 yr but not progressions or deaths. The benefit of the two additional years of maintenance should be weighed against its added costs and inconvenience.
Keywords: Non-muscle invasive bladder cancer; Randomized Controlled Trial; Immunotherapy; Bacillus Calmette-Guerin; Adjuvant treatment; Urinary bladder; Maintenance therapy; TRANSITIONAL-CELL CARCINOMA; TRANSURETHRAL RESECTION; UROTHELIAL CARCINOMA; MITOMYCIN-C; FOLLOW-UP; 27 MG; TRIAL; TUMORS; PROGRESSION; EFFICACY